Genetic Characterization of African Swine Fever Virus from Pig Farms in South Korea during Outbreaks in 2019–2021 - Ki-Hyun Cho; Da-Young Kim; Min-Kyung Jang; Seong-Keun Hong; Ji-Hyoung Ryu; Hae-Eun Kang; Jee-Yong Park (Viruses, 2022)
In South Korea, a total of 21 African swine fever (ASF) infected farms were confirmed during 2019–2021. ASF viruses (ASFVs) were isolated from the blood and spleen samples of the 21 affected farms and their genetic characteristics were analyzed. Phylogenetic analysis indicated that the 21 Korean ASFV strains belonged to p72 genotype II and serogroup 8. All isolates were of the intergenic region (IGR) II variant with 10 tandem repeat sequences between I73R and I329L and the central variable region (CVR) 1 variant of the B602L gene. There were no IGR variations between the A179L and A137R and between the MGF 505 9R and10R nor mutations in the O174L, K145R, MGF 505-5R, CP204L, and Bt/Sj regions. The genes of the 21 ASFV strains were identical to those of Georgia 2007/1 and Chinese and Vietnamese strains (Pig/HLJ/2018, China/2018/AnhuiXCGQ, and ASFV_NgheAn_2019); however, X69R of the J268L region of the 18th isolate (Korea/Pig/Goseong/2021) had three nucleotide (CTA) insertions at the 209th position, which led to the addition of one tyrosine (Y) at the C-terminal. This suggests that there are variations among ASFVs circulating in South Korea and the 18th ASFV-infected farm was due to a variant different from those of the other 20 pig farms.